The warrior maiden : a Hopi legend - Schecter, Ellen; Kelly, Laura (Milwaukee : Gareth Stevens Publishing, 1997)
A retelling of the Indian legend in which Huh-ay-ay, a brave Hopi girl, helps to save her peaceful pueblo from Apache raiders.
"A Byron Preiss book."
Originally published: New York : Bantam Books, c1992.
Keywords: Hopi Indians -- Folklore; Folklore -- Arizona; Indians of North America -- Folklore. -- Arizona